(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Calprotectin a calcium and zinc binding protein, is a breakdown product of WBC which can be detected and quantified in both stool and plasma and is markedly elevated in infectious and inflammatory conditions, including inflammatory bowel disease (IBD). Reference ranges for faecalcalprotectin (FC) have been established in healthy adults and children and elevated concentrations of FC have been demonstrated in numerous studies of patients with IBD. The overall sensitivity and specificity for FC in IBD found to be as high as 78-100% and 76-100% respectively. The FC correlates well with histological inflammation as detected by colonoscopy with biopsies and has been shown successfully to predict relapses in patients with IBD. The FC has been shown to consistently differentiate IBD from irritable bowel syndrome (IBS) because it has excellent negative predictive value in ruling out IBD in undiagnosed, symptomatic patients. The FC may be also useful in determining whether clinical symptoms in patients with known IBD are caused by disease flares or non inflammatory complications/underlying IBS and in providing objective evidence of response to treatment. Although more studies are needed to define fully the role of FC, convincing studies and growing clinical experience point to an expanded role in the diagnosis and management of IBD. J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 58-64